Evaluation of Dental Holder Innovation: Patient Comfort and Periapical Intra-Oral Radiographic Image Quality - Jannah, Marichatul; Prakoso, Dimas; Erfansyah, Muhammad (Jurnal Riset Kesehatan, 2024)
This study evaluates an innovative dental holder designed to improve patient comfort and radiographic image quality in intra-oral periapical examinations. Conducted at Muhammadiyah University Semarang Dental and Oral Hospital, the research involved 30 patients who used the modified holder featuring a 20-degree tilt, biocompatible PLA material, and silicone pads. Results showed that 73.33% of patients experienced no nausea, and 93.33% had no allergic reactions, highlighting the holder's safety and comfort. Although 56.67% reported excessive oral pressure, 60% noted reduced pain due to the silicone pads. The holder also improved image quality, with 76.67% of patients acknowledging clear apical images, and 100% reporting no distortion or blurring. The study indicates that while the holder significantly enhances patient comfort and image quality, further design adjustments are needed to address size-related issues. Future developments should focus on customizing the holder for local anatomical variations and exploring additional eco-friendly materials. Enhanced training for practitioners and further research with diverse populations are recommended to optimize the holder's effectiveness.